Facile synthesis of ZnFe2O4 photocatalysts for decolourization of organic dyes under solar irradiation - Behera, Arjun; Kandi, Debasmita; Majhi, Sanjit Manohar; Martha, Satyabadi; Parida, Kulamani (Beilstein Journal of Nanotechnology, 2018)
ZnFe2O4 was fabricated by a simple solution-combustion method. The structural, optical and electronic properties are investigated by XRD, TEM, FESEM, UV–vis DRS, PL, FTIR and photocurrent measurements. The photocatalytic activity of the prepared material is studied with regard to the degradation of rhodamine B (Rh B) and Congo red under solar irradiation. The kinetic study showed that the material exhibits zeroth and first order reaction kinetics for the degradation of Rh B and Congo red, respectively. The photocatalytic behaviour of ZnFe2O4 was systematically studied as a function of the activation temperature. ZnFe2O4 prepared at 500 °C showed the highest activity in degrading Rh B and Congo red. The highest activity of ZnFe2O4-500 °C correlates well with the lowest PL intensity, highest photocurrent and lowest particle size.
Keywords: Congo red; electrochemical study; phenol; photocatalyst; rhodamine B (Rh B); ZnFe2O4